Illicit Small Arms Prices: Introducing Two New Datasets. Issue 4 (19th May 2021) - Marsh, Nicholas J.; McDougal, Topher L.
ABSTRACT: Despite calls to reduce illicit arms flows, it remains difficult to detect and quantify them. One proposed method for detecting and quantifying illicit trade volumes is to test econometrically for price changes. This paper documents an effort of the Peace Research Institute Oslo (PRIO) and the Small Arms Data Observatory (SADO) to make such inferential econometric analyses possible by assembling two new datasets on illicit small arms prices. The first, called the 'Illicit Small Arms Prices – Transactions' dataset (iSAP-T), has an observational unit of arm(s) sold in a single transaction. The second, called the 'Illicit Small Arms Prices – Countries' dataset (or iSAP-C), derives from the iSAP-T and has the more standard country-year observational unit. This paper describes the methods for data collection, organization, and generation for these datasets, presents some descriptive statistics and graphics, and concludes with a discussion of possible future uses and limitations of the datasets.